PERLINDUNGAN HUKUM ATAS HAK UNTUK MELANJUTKAN KETURUNAN DALAM SURROGATE MOTHER - Maria Yolanda Jeli Monez (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2020)
Surrogate mother is an extension of the IVF method known as the uterine lease agreement, which is an agreement between a woman who ties herself through an agreement with another party (husband and wife) to become pregnant with the result of the fertilization of the husband and wife implanted into her womb, and after giving birth is required to submit the baby to the husband and wife based on the agreement made. But the legality of surrogate mother must be questioned. This, concerns someone who uses the seeds of his partner or a woman who has no relationship, or conversely a woman who is fertilized with another seed who is not her husband, in the sense of not being bound by marital relations. So this can be subject to criminal law.Nonetheless, the right to continue heredity is a human right inherent in every individual. Continuing descent is a function of family institutions.In Indonesia, the Raahim rental agreement has not been regulated and is legally prohibited, but in practice many things have been done secretly. Therefore, without contradicting the two issues above, it is considered necessary to provide legal protection for husband and wife who make surrogate mother agreements in an effort to continue the descent as a Human Rights. Keywords: Surrogate Mother, Human Rights, Uterus Rent, Heredity